Adresat v âzykovoj kommunikacii - Formanovskaâ, N. I. (Stylistyka, 2021)
The paper describes the parameters of verba I communication with the addressee playing an active part as: I ) the addresser’s coauthor when choosing the topie, the style, the genre, the metalanguage etc.; 2) the recipient, who receives, understands and interprets the message, and has common background cultural knowledge and presuppositions with the addresser; 3) the respondent dependant on the preceding discourse/text; The classification of the types of addressees is suggested. Thus the addressee is regarded as an active, next to the addresser, participant of verbal communication.